2022
DOI: 10.1155/2022/2681278
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation of the Effects of Large Bone Flap Craniotomy on Cerebral Hemodynamics, Intracranial Infection Rate, and Nerve Function in Patients with Severe Craniocerebral Trauma

Abstract: In order to explore the clinical value of large bone flap craniotomy, the effects of standard large bone flap craniotomy on cerebral hemodynamic indexes, incidence of postoperative intracranial infection, and neurological function in patients with severe craniocerebral trauma are investigated. 89 patients with severe craniocerebral trauma admitted from January 2020 to June 2021 are analyzed retrospectively. All patients are divided into a large craniotomy group (n = 45) and control group (n = 44) according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Traumatic brain injury (TBI) is defined as an acquired insult to the brain caused by an external mechanical force, which may contribute to temporary or permanent impairment (Capizzi et al., 2020). With the rapid development of industry and transportation, the rate of accidents is increasing year by year, accompanied by the increased number of patients with craniocerebral trauma, and severe traumatic brain injury (sTBI), as a common type of disease in neurosurgery, often results in the loss of nerve function, contributing to severe disturbance of consciousness, seizures, aphasia, hemiplegia and even a long‐term vegetative state (Li et al., 2022). Due to the rapid onset and development of craniocerebral trauma, patients need to be resuscitated in a timely manner, and craniotomy is one of the primary treatments for sTBI; it can effectively remove intracranial haematomas and reduce mortality, but is prone to postoperative hydrocephalus (Rufus et al., 2021; Wani et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is defined as an acquired insult to the brain caused by an external mechanical force, which may contribute to temporary or permanent impairment (Capizzi et al., 2020). With the rapid development of industry and transportation, the rate of accidents is increasing year by year, accompanied by the increased number of patients with craniocerebral trauma, and severe traumatic brain injury (sTBI), as a common type of disease in neurosurgery, often results in the loss of nerve function, contributing to severe disturbance of consciousness, seizures, aphasia, hemiplegia and even a long‐term vegetative state (Li et al., 2022). Due to the rapid onset and development of craniocerebral trauma, patients need to be resuscitated in a timely manner, and craniotomy is one of the primary treatments for sTBI; it can effectively remove intracranial haematomas and reduce mortality, but is prone to postoperative hydrocephalus (Rufus et al., 2021; Wani et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%